Original paper Squamous cell carcinoma of the nail apparatus in the population of Northern Poland - Sobjanek, Michał; Michajłowski, Igor; Malek, Marta; Biernat, Wojciech; Włodarkiewicz, Adam; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction: Malignant tumours of the nail apparatus in Caucasian population are rare. Among them melanoma and squamous cell carcinoma (SCC) are the most common diagnoses. Non-characteristic clinical feature of nail apparatus SCC (NSCC) may mimic various inflammatory and infectious diseases. Tumour is often misdiagnosed what causes delay of the treatment. Aim: Investigation on frequency, clinical and histopathological characteristics of NSCC in a Northern Poland population. Material and methods : One thousand five hundred and eighty-eight patients with various nail apparatus pathology who were referred to the Department of Dermatology, Venerology and Allergology, Medical University of Gdansk, from 2005 to 2010, were included in the study. Among all these patients 12 cases of nail apparatus maligancy were diagnosed including 4 cases of NSCC. Results: The NSCC was observed in 0.25% of the patients with nail pathology. Tumour affected only men. Mean age came to 58.3 years old. The median delay to diagnosis was 21 months what was caused by mistaken initial diagnosis in 3 cases. The most frequent localization was the thumb of dominant hand. Relapses after surgical treatment were not observed. Follow-up lasted from 2 to 5 years. Conclusions: The incidence of NSCC in Caucasian population is low. Tumours may mimic other benign conditions so histopathologic examination is fundamental. Wide surgical excision and micrographic surgery still seem to be the first line treatment in local invasive NSCC.